Effects of nanocrystalline hydroxyapatite concentration and skeletal site on bone and cartilage formation in rats. (August 2021) - Boller, Lauren A.; Shiels, Stefanie M.; Florian, David C.; Peck, Sun H.; Schoenecker, Jonathan G.; Duvall, Craig; Wenke, Joseph C.; Guelcher, Scott A.
Abstract: Most fractures heal by a combination of endochondral and intramembranous ossification dependent upon strain and vascularity at the fracture site. Many biomaterials-based bone regeneration strategies rely on the use of calcium phosphates such as nano-crystalline hydroxyapatite (nHA) to create bone-like scaffolds. In this study, nHA was dispersed in reactive polymers to form composite scaffolds that were evaluated both in vitro and in vivo . Matrix assays, immunofluorescent staining, and Western blots demonstrated that nHA influenced mineralization and subsequent osteogenesis in a dose-dependent manner in vitro . Furthermore, nHA dispersed in polymeric composites promoted osteogenesis by a similar mechanism as particulated nHA. Scaffolds were implanted into a 2-mm defect in the femoral diaphysis or metaphysis of Sprague-Dawley rats to evaluate new bone formation at 4 and 8 weeks. Two formulations were tested: a poly(thioketal urethane) scaffold without nHA (PTKUR) and a PTKUR scaffold augmented with 22 wt% nHA (22nHA). The scaffolds supported new bone formation in both anatomic sites. In the metaphysis, augmentation of scaffolds with nHA promoted an intramembranous healing response. Within the diaphysis, nHA inhibited endochondral ossification. Immunohistochemistry was performed on cryo-sections of the bone/scaffold interface in which CD146, CD31, Endomucin, CD68, and Myeloperoxidase were evaluated. No significant differences in the infiltrating cell populations were observed. These findings suggest that nHA dispersed in polymeric composites induces osteogenic differentiation of adherent endogenous cells, which has skeletal site-specific effects on fracture healing. Statement of significance: Understanding the mechanism by which synthetic scaffolds promote new bone formation in preclinical models is crucial for bone regeneration applications in the clinic where complex fracture cases are seen. In this study, we found that dispersion of nHA in polymeric scaffolds promoted in vitro osteogenesis in a dose-dependent manner through activation of the PiT1 receptor and subsequent downstream Erk1/2 signaling. While augmentation of polymeric scaffolds with nHA enhanced intramembranous ossification in metaphyseal defects, it inhibited endochondral ossification in diaphyseal defects. Thus, our findings provide new insights into designing synthetic bone grafts that complement the skeletal site-specific fracture healing response. Graphical abstract: Image, graphical abstract